2009
DOI: 10.1016/j.neuropharm.2008.09.009
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor-mediated long-term alterations in epileptiform activity in experimental chronic epilepsy

Abstract: When epileptiform activity is acutely induced in vitro, transient partial blockade of N-methyl-Daspartic acid (NMDA) receptor-mediated calcium influx leads to selective long-term depotentiation of the synapses involved in the epileptic activity as well as a reduction in the probability of further epileptiform activity. If such selective depotentiation occurred within foci of epileptic activity in vivo, the corresponding long-term reduction in seizure probability could form the basis for a novel treatment of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 57 publications
4
17
0
1
Order By: Relevance
“…On the other hand, PP2B inhibition might also have its effects over several brain receptors function and composition. This effect was also previously described in other animal models (Hellier et al 2009;Lau and Zukin 2007), and resulted to be modified after ASC action in our model. The postsynaptic density is rich in PP2B, and NMDA receptor, AMPA/kainate glutamate receptors, and GABAA receptor have been identified as either direct or indirect substrates regulated by PP2B.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, PP2B inhibition might also have its effects over several brain receptors function and composition. This effect was also previously described in other animal models (Hellier et al 2009;Lau and Zukin 2007), and resulted to be modified after ASC action in our model. The postsynaptic density is rich in PP2B, and NMDA receptor, AMPA/kainate glutamate receptors, and GABAA receptor have been identified as either direct or indirect substrates regulated by PP2B.…”
Section: Discussionsupporting
confidence: 86%
“…It has been reported that phosphorylated NMDA receptor subtype 2B (NR2B) can increase Ca 2+ permeability through NMDA receptors [30]. NR2B has been identified as an indicator of intracellular Ca 2+ influx that is activated by seizures [31].…”
Section: Discussionmentioning
confidence: 99%
“…Another challenge is that the mechanism of seizure generation, and therefore response to potential therapeutic interventions, is still poorly understood and may vary between subjects. While suppression of local activity within a seizure focus might be intended to serve as a functional lesion, network regulation and long-term plasticity have also been hypothesized as potential seizure suppression mechanisms (Hellier et al 2009). In contrast to the ability to manipulate the clinical stimulation device in our epileptic NHP over multiple experiments, human studies of direct hippocampal stimulation have almost exclusively branched from an initial report of 10 patients undergoing intracranial monitoring.…”
Section: Discussionmentioning
confidence: 99%